Anti-CMV therapy, what next? A systematic review - Gourin, Claire; Alain, Sophie; Hantz, Sébastien (Frontiers in Microbiology, 2023)
Human cytomegalovirus (HCMV) is one of the main causes of serious complications in immunocompromised patients and after congenital infection. There are currently drugs available to treat HCMV infection, targeting viral polymerase, whose use is complicated by toxicity and the emergence of resistance. Maribavir and letermovir are the latest antivirals to have been developed with other targets. The approval of letermovir represents an important innovation for CMV prevention in hematopoietic stem cell transplant recipients, whereas maribavir allowed improving the management of refractory or resistant infections in transplant recipients. However, in case of multidrug resistance or for the prevention and treatment of congenital CMV infection, finding new antivirals or molecules able to inhibit CMV replication with the lowest toxicity remains a critical need. This review presents a range of molecules known to be effective against HCMV. Molecules with a direct action against HCMV include brincidofovir, cyclopropavir and anti-terminase benzimidazole analogs. Artemisinin derivatives, quercetin and baicalein, and anti-cyclooxygenase-2 are derived from natural molecules and are generally used for different indications. Although they have demonstrated indirect anti-CMV activity, few clinical studies were performed with these compounds.Immunomodulating molecules such as leflunomide and everolimus have also demonstrated indirect antiviral activity against HCMV and could be an interesting complement to antiviral therapy. The efficacy of anti-CMV immunoglobulins are discussed in CMV congenital infection and in association with direct antiviral therapy in heart transplanted patients. All molecules are described, with their mode of action against HCMV, preclinical tests, clinical studies and possible resistance. All these molecules have shown anti-HCMV potential as monotherapy or in combination with others. These new approaches could be interesting to validate in clinical trials.